Article Review: Neuroendocrine Interplay: How Hormones Shape Human Psychology and Mental Disorders - M. J, Jiheel (American Journal of Biomedicine and Pharmacy, 2025)
This article examines the critical link between hormones and psychological states, essential for understanding mental health and behavior. It notes that aggressive behavior in psychiatric patients may stem from hormonal imbalances and surveys prevalent mental disorders worldwide—including anxiety disorders (excessive fear), depression (persistent low mood), bipolar disorder (extreme mood swings), PTSD (post-trauma effects), and schizophrenia (disrupted cognition and behavior), alongside eating and behavioral disorders. Affecting millions globally, these conditions highlight the need to explore their biological and psychological underpinnings. Hormones, defined as chemical messengers from endocrine glands, regulate bodily functions via the bloodstream. Beyond simple signaling, they intricately modulate growth, metabolism, homeostasis, mood, and emotions. Key hormones influencing mental health include: serotonin (mood and anxiety regulation), cortisol (stress response), dopamine (reward and motivation), oxytocin (social bonding), melatonin (sleep cycles), and ghrelin/leptin (appetite control). Imbalances in these systems can trigger mental health disorders. The article underscores that deciphering hormone-psychology interactions is vital for advancing mental health treatments and improving well-being.